Library Audiobook System Using Speech Recognition - et. al., Nikhat Parveen. (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Developments in man-made consciousness are beginning to be used successfully in human life, enabled by the use of things in different ways. Independent devices are becoming more cunning in their way of communicating in modern ways by using new technologies. The invention of perceiving modern technology to a person is one of the useful trends. For voice recognition, this project presents an exceptionally on-demand, fast, and user-friendly Python using Visual Studio Code. This software helps transform text to speech and vice versa. Voice or some other type of voice can be converted into the text instead of tapping on a keyboard. Any kind of voice message can be stated in this app as the input, and the corresponding text will appear on the screen. Modern technology can easily generate text. The recognized text can be stored in a file with GUI/Voice command. This application useful for people with physical disabilities like deaf or handicapped users who are often difficult, painful, or impossible to type, and also for people who can understand while others speaking but cannot read the words.